Biomechanical analysis of two runners who developed leg injuries during a six-week transition to maximal running shoes: A case series - Hannigan, J. J.; Pollard, C. D. (Journal of Sports Sciences, 2021)
Achilles tendinopathy (AT) and medial tibial stress syndrome (MTSS) are two of the most common running-related injuries. In a previous study investigating running biomechanics before and after a six-week transition to maximal running shoes, two runners dropped out of this study due to Achilles pain and shin pain, respectively. The purpose of this case series was to investigate running biomechanics in those two runners, identifying potential causes for injury in relation to maximal shoe use. Running biomechanics were collected in a laboratory setting for these two runners wearing both a maximal running shoe and traditional running shoe before the six-week transition using an 8-camera motion capture system and two embedded force plates. Both runners displayed prolonged eversion in the maximal shoe, which has been previously cited as a potential risk factor for developing Achilles tendinopathy and medial tibial stress syndrome. Relatively high loading rates and impact forces were also observed in the runner with shin pain in the maximal shoe, which may have contributed to their pain. More prospective research on injury rates in individuals running in maximal shoes is needed.